Analysis Of The Impact Of Rice Imports, Rice Consumption, Productivity, Harvest Area, And Rice Production On The Farmer's Exchange Rate For Food Crops In 2019-2023 - Nurina Endra Purnama; Fathan Muhammad; Jooner Rambe (International Journal of Economics, Commerce, and Management, 2024)
Rice imports have been demonstrated to influence the Farmer's Exchange Rate (NTP) significantly. A reduction in rice imports by 356,286.2 tons in 2020 corresponded with a decline in NTP to 101.65. In contrast, per capita, weekly rice consumption did not exhibit a statistically significant impact on NTP, as evidenced by the lowest consumption in 2019 (1.504 kg), while the NTP remained at 104.46. On the other hand, rice productivity was found to have a notable influence on NTP, with trends in productivity closely mirroring those of the NTP. The harvest area, however, did not present a significant correlation with NTP, as demonstrated in 2019 when an increase in harvest area did not prevent the NTP from remaining at a lower level of 104.46. Lastly, rice production had a significant effect on NTP, with increases in production during 2021 and 2022 leading to subsequent increases in the NTP.